Inclusiveness and Exclusiveness of Japanese-Style Management Abroad - Some Evidence from South East Asia - Diefenbach, Thomas (The South East Asian Journal of Management, 2015)
Research has shown that, when Japanese companies go abroad, they continue to apply their distinctive Japanese-style management – with perhaps some adaptation to local economic and socio-cultural contexts. What has not been researched so far is how inclusive or exclusive Japanese-style management is for those working within the organisation. Based on case studies carried out in eight Japanese companies in Cambodia, Thailand and Vietnam, this paper investigates how Japanese and local managers and employees are either included or excluded by the values, management styles and ways of decision-making prevailing in their company. The evidence not only shows differences in perceptions but also reveals some questionable aspects of Japanese-style management. It seems to be much more exclusive than suggested by either most stereotypical research on or popular understanding of Japanese management.